Ecofriendly management of coconut root grub Leucopholis coneophora Burm. - Jeevan, C.H.; Sreekumar, K.M. (Journal of Tropical Agriculture, 2016)
Bio-agents, botanicals and novel insecticides were evaluated against coconut root grub during 2012-14 at College of Agriculture, Padnekkad, Kasaragod, Kerala. Laboratory experiments, field pot experiments and field cage experiments were conducted to identify ecofriendly management measures. Cent per cent mortality of grubs was observed in case of grubs treated with the Novaluron10 EC 0.05%, Clothianidin 30 WDG 8.23 x 102 g ai ha-1 and Azadirachtin 1500 ppm at 5, 10 and 15ml per litre as well as in case of grubs treated with Malathion 50 EC 0.1%. CNSL (Cashew Nut Shell Liquid) 2% and Chlorpyrifos 20 EC 0.02% recorded 80 and 66 per cent mortality respectively. In the pot studies, maximum mortality of 98 per cent was observed in treatments with Azadirachtin 10ml l-1 and 15ml l-1 followed by Malathion with 97 per cent and Clothianidin with 87 % mortality. In the cage studies, the treatment Azadirachtin 15ml l-1 gave highest mortality (97 %) followed by Malathion (87%), Clothianidin (73%), Azadirachtin10ml l-1 (70%) and Azadirachtin 5ml l-1 (63%). There was no mortality in absolute control. The EPN Heterorhabditis indica inflicted no mortality.